Give Scratch an Abstraction Mechanism. - Naur, Thorkil; Brahes, Karen (Communications of the ACM, 2010)
The article presents a letter to the editor commenting on the article "Scratch: Programming for All" by Michel Resnick et al, published in the November 2009 edition of the journal.